Modern Methods of Treatment for Idiopathic (Immune) Thrombocytopenic Purpura (ITP) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Idiopathic (immune) thrombocytopenic purpura (ITP) is an autoimmune disorder characterized by isolated thrombocytopenia, leading to increased risk of bleeding. Despite decades of use of corticosteroids, intravenous immunoglobulin (IVIG), and splenectomy, many patients experience relapse or become dependent on long-term therapy. In recent years, novel treatments – particularly thrombopoietin-receptor agonists (TPO-RAs), monoclonal antibodies (e.g., anti-CD20), and small-molecule inhibitors – have expanded therapeutic options. This review synthesises data from randomized trials, cohort studies, meta-analyses, and clinical guidelines published between 2015 and 2024, evaluating both efficacy and safety of traditional and emerging therapies. Findings reveal that TPO-RAs achieve durable platelet response in a majority of chronic ITP patients; monoclonal antibody therapies and splenectomy remain important in selected cases. Emerging agents show promise but require further long-term evaluation. The review highlights the importance of individualized therapy and outlines future research directions.